2017
DOI: 10.1186/s41182-017-0044-y
|View full text |Cite
|
Sign up to set email alerts
|

Malaria impact of large dams at different eco-epidemiological settings in Ethiopia

Abstract: BackgroundDams are important to ensure food security and promote economic development in sub-Saharan Africa. However, a poor understanding of the negative public health consequences from issues such as malaria could affect their intended advantages. This study aims to compare the malaria situation across elevation and proximity to dams. Such information may contribute to better understand how dams affect malaria in different eco-epidemiological settings.MethodsLarval and adult mosquitoes were collected from da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 35 publications
3
56
4
Order By: Relevance
“…The diversity of mosquito breeding habitats in the irrigated area was two-fold higher than the non-irrigated area, indicating that the irrigation development contributed to the proliferation of malaria mosquito breeding habitats. Improper ground excavation, frequent vehicles and machineries movements during planting and harvesting, lack of maintenance and poor environmental management contributed to the formation of numerous mosquito breeding habitats in the irrigation project area as noted elsewhere in Africa [5,20,21]. Similarly, several studies elsewhere in Africa have suggested that changes in land use have influenced malaria vector larval habitat availability and distribution [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of mosquito breeding habitats in the irrigated area was two-fold higher than the non-irrigated area, indicating that the irrigation development contributed to the proliferation of malaria mosquito breeding habitats. Improper ground excavation, frequent vehicles and machineries movements during planting and harvesting, lack of maintenance and poor environmental management contributed to the formation of numerous mosquito breeding habitats in the irrigation project area as noted elsewhere in Africa [5,20,21]. Similarly, several studies elsewhere in Africa have suggested that changes in land use have influenced malaria vector larval habitat availability and distribution [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…This seems to suggest that, while high coverage levels of the various interventions are desired, equally important are the uptake of these interventions that ultimately increases the levels of PE which will lead to further reductions of predicted incidence of malaria cases in the various zones. The presence of community water reservoirs such as irrigation dams or dug-outs could potentially adversely affect the burden of malaria particularly a rise in incidence of malaria despite their potential socio-economic benefits to the communities they are situated [32][33][34]. In this respect, the promise of the Government of Ghana to build community level dams/dag-outs/ponds in various districts of the country, under the one village one dam policy [35][36][37], could pose a risk to the gains already made in reducing the burden of malaria if appropriate dam management practices are not applied after they are commissioned.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, presence of cattle and other animals in the vicinity that serve as an alternative source of mosquito blood meal might also contribute to the outdoor feeding tendency of anopheline mosquitoes in the study area. A targeted larval source management in the irrigated elds could help reduce vector density/abundance both indoors and outdoors [34]. Irrigation schemes should therefore consider additional vector management strategies to mitigate malaria vector breeding in such settings.…”
Section: Discussionmentioning
confidence: 99%